Dermatomyositis: difficuities of diagnostic search - M. M. Tlish; Zh. Yu. Naatyzh; T. G. Kuznetsova (Лечащий Врач)
Dermatomyositis is a systemic disease, mainly of autoimmune Genesis, which is characterized by lesions of skeletal and smooth muscles, skin and mucous membranes. The multi-organ nature of the pathological process determines the polymorphism of clinical manifestations of the disease. In addition to pathognomonic symptoms for dermatomyositis, in the form of gradually increasing lesions of striated muscles, heliotropic rash, symptoms of Gottron and Keining, the disease is also characterized by a large number of malospecific changes. Often, hyperkeratosis, atrophy, vesicular-bullous and ulcerative rashes, dysphagia and reflux esophagitis, colitis and enteritis, pneumonia, fibrous alveolitis and hypoventilation syndrome, heart lesions become dominant. To date, the disease is considered as an idiopathic immune-mediated pathological process that develops in the presence of a genetic predisposition in response to the action of provoking environmental factors. Among hereditary markers of dermatomyositis, changes in the major histocompatibility complex, as well as in genes encoding cytokines, have been described. Trigger factors can be long-term chronic infections, physical and mental trauma, hyperinsolation, vaccination, and certain medications. Numerous cases of combination of dermatomyositis with oncological pathology and systemic connective tissue diseases are described in the literature. The scarcity and low specificity of the symptoms of the disease can lead to a long diagnostic search, while the involvement in the pathological process of several body systems makes patients turn to doctors of various profiles. Thus, dermatomyositis is an interdisciplinary problem, hence the increased awareness of doctors of related specialties can contribute to clinical alertness. In this regard, we present our own observation of a patient with dermatomyositis, which was accompanied by atypical rashes, polysyndromnostyu, as well as the absence of myositis-specific autoantibodies, which required an expanded laboratory and instrumental diagnosis (including to exclude paraneoplastic polymyositis).